Epithelial alarmin levels in exhaled breath condensate in patients with idiopathic pulmonary fibrosis: A pilot study. (19th August 2019) - Majewski, Sebastian; Tworek, Damian; Szewczyk, Karolina; Kurmanowska, Zofia; Antczak, Adam; Górski, Paweł; Piotrowski, Wojciech Jerzy
Abstract: Introduction: Interleukin (IL)‐25, IL‐33 and thymic stromal lymphopoietin (TSLP) are epithelial alarmins involved in innate immune responses and have been shown to play an important role in chronic lung diseases. No data are available regarding their levels in exhaled breath condensate (EBC) in idiopathic pulmonary fibrosis (IPF). Objectives: To examine IL‐25, IL‐33 and TSLP levels in the EBC obtained from patients with IPF and compare them to those in healthy controls, patients with asthma and chronic obstructive pulmonary disease (COPD). Methods: Twenty‐three patients with asthma, 25 patients with COPD, 15 patients with IPF and 16 healthy controls were studied. Concentrations of alarmins in the EBC were evaluated by means of ELISA. Results: IL‐25 EBC levels were numerically lowest in IPF (25.33 ± 8.84 pg/ml). However, they did not differ significantly from healthy subjects (43.18 ± 5.53 pg/ml), but were significantly lower compared to asthma (72.07 ± 6.03 pg/ml; P < .001). IL‐33 EBC levels were significantly increased in IPF (3.41 ± 0.55 pg/ml) compared to healthy controls (1.20 ± 0.60 pg/ml; P < .01) but did not differ from asthma (3.68 pg/ml) and COPD levels (2.47 ± 0.34 pg/ml). There were significant correlations between IL‐33 EBC levels and lung diffusion capacity of carbon monoxide (DLco ) absolute ( r = .63; P < .05) and % of predicted values ( r = .67; P < .01) as well as with time since diagnosis ( r = −.59; P < .05) in IPF subjects. TSLP was undetectable in examined samples. Conclusion: IL‐25 and IL‐33 are detectable in the EBC obtained from IPF subjects. Increased levels of IL‐33 compared to healthy controls indicate its possible role in the pathobiology of IPF.